The association between Memorial Sloan Kettering Frailty Index with 30-day survival among patients aged ≥ 75 with cancer and COVID-19. Issue 4 (May 2022) - Kim, Soo Jung; Fessele, Kristen L.; Tin, Amy L.; Malling, Charlotte; Litchfield, Hayley; Korc-Grodzicki, Beatriz; Shahrokni, Armin
Abstract: Background: Advanced age and multiple comorbidities have been established as a risk factor for more severe disease and increased mortality among patients with COVID-19, yet the impact of frailty in patients with cancer 75 years and older who are admitted, remains unclear. Methods: To better understand the clinical presentation and course of illness for this population, we conducted a chart review of patients with cancer age 75 and older who were admitted to a comprehensive cancer center within 72 h of a confirmed COVID-19 diagnosis over a three-month period (March 1, 2020-May 31, 2020). Frequency and proportion of characteristics were reported. We additionally assessed the association between frailty and 30-day mortality using univariable logistic regression. Results: Our cohort consisted of 70 patients. We found evidence that increased frailty based on MSK-FI was associated with increased risk of 30-day mortality (OR 1.37, 95% CI 1.00, 1.87; p -value = 0.051), though this did not meet conventional levels of significance. Conclusion: Our analysis showed evidence of some association between degree of frailty and 30-day survival among older patients with cancer aged ≥75 who were admitted with COVID-19 infection. This finding illustrates the importance of frailty screening in the care management of older patients with cancer and COVID-19.